The mysterious spheres on Greek and Roman ancient coins - Sidrys, Raymond V., (Archaeopress Publishing Ltd, 2020)
This is not a standard coin catalogue, but it focuses on quantities and percentages of the mysterious 5950 sphere images on Roman coin reverses, and a few Greek coins. This research identifies political, cultural, religious and propaganda trends associated with the coin sphere images, and offers a variety of new findings.